Examining Education Management System at a State Madrasah Aliyah in Jambi: Concerning Leadership, Budgeting, and Accreditation - Jamrizal Jamrizal (AL-ISHLAH: Jurnal Pendidikan, 2023)
In this study, a quantitative investigation is employed to find out the relationship among three pivotal components of the education management system at a state Madrasah Aliyah in Jambi, namely its budget, leadership, and accreditation. The IBM SPSS version 27 application is used in this research as the quantitative data analysis method. 91 respondents comprised the study’s population, and 46 respondents comprised the sample overall. The respondents were taken by using the sampling technique known as accidental sampling to establish the research sample. In this investigation, the t-test, F test, and coefficient of determination test were all run. The findings of this study show that: 1) accreditation has a large impact on education management; 2) leadership has a significant impact on education management; and 3) budgeting has a substantial impact on education management. and 4) Accreditation, Leadership and Budgeting simultaneously have a significant effect on Education Management.